Espécies do gênero Argulus (Crustacea - Branchiura - Argulidae) da coleção do Museu Nacional do Rio de Janeiro - Trancoso, Nadir Schotz da Silveira (1980)
Some general considerations are given concerning sistematics, nomenclature, zoogeographical distribution, the parasite-host relation ship of the brazilian argulids (Crustacea-Branchiura). The study embraces six species, three are recorded for the first time for our crustacean fauna. Twelve plates illustrates this work.